2015
DOI: 10.1007/s12134-015-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Hope as a Crucial Factor in Integration Among Unaccompanied Immigrant Youth in the USA: A Pilot Project

Abstract: In 2014, 53,518 unaccompanied immigrant youth, predominantly from Central America, arrived in the USA. By mid-2015, over 12,000 had already arrived (Office of Refugee Resettlement 2015). Despite experiencing a myriad of risk factors and challenges, these children display remarkable resiliency. An important component of this resiliency which, in turn, enhances the well-being of these populations, is the maintenance of hope. This paper reports on a study conducted in spring 2013 on the presence of hope among 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Family is a key source of social support for children. Evidence consistently supports the role of family ties as an asset and positive parent–child relationships as a source of strength, protection and security for children (Bermudez et al, 2018; Bettmann & Olson‐Morrison, 2018; Eruyar, Maltby, & Vostanis, 2020; Lauritzen & Sivertsen, 2012; McGregor et al, 2016; Nasıroğlu et al, 2018; Oppedal & Idsoe, 2015; Veronese & Castiglioni, 2015; Veronese et al, 2018; Veronese, Pepe, Jaradah, Murannak, et al, 2017; Zwi et al, 2018) Unaccompanied refugee children who have contact with their families living abroad perceive high levels of support and present with lower levels of depression, despite lack of physical contact and face‐to‐face communication with families (Eriksson & Rundgren, 2019; Jani, Underwood, & Ranweiler, 2016; Oppedal & Idsoe, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family is a key source of social support for children. Evidence consistently supports the role of family ties as an asset and positive parent–child relationships as a source of strength, protection and security for children (Bermudez et al, 2018; Bettmann & Olson‐Morrison, 2018; Eruyar, Maltby, & Vostanis, 2020; Lauritzen & Sivertsen, 2012; McGregor et al, 2016; Nasıroğlu et al, 2018; Oppedal & Idsoe, 2015; Veronese & Castiglioni, 2015; Veronese et al, 2018; Veronese, Pepe, Jaradah, Murannak, et al, 2017; Zwi et al, 2018) Unaccompanied refugee children who have contact with their families living abroad perceive high levels of support and present with lower levels of depression, despite lack of physical contact and face‐to‐face communication with families (Eriksson & Rundgren, 2019; Jani, Underwood, & Ranweiler, 2016; Oppedal & Idsoe, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of psychopathology in refugee children is associated with both current and previous nuclear family separation (Eriksson & Rundgren, 2019; Jani et al, 2016; Longobardi et al, 2017; Mace, Mulheron, Jones, & Cherian, 2014; McGregor et al, 2016; Thommessen et al, 2015) and parentless status (Khan et al, 2019; Zwi et al, 2018). Unaccompanied refugee children frequently speak of the emotional difficulty separation from family brings into their lives (Eriksson & Rundgren, 2019; Jani et al, 2016; McGregor et al, 2016). Connection or unification with the family is viewed as a key source of social support and emotional safety (Eriksson & Rundgren, 2019; Jani et al, 2016; McGregor et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In qualitative, mixed methods, and quantitative literature, family reunification was a major reason why Central American minors migrated unaccompanied and undocumented. For example, quantitative studies by several scholars found that familial connections drove the undocumented migration of youth (Anastario et al, 2015; Donato & Sisk, 2015; Jani et al, 2016; Jones, 2017; Lorenzen, 2017). Thus, the findings from these studies connect with other similar types of research on the undocumented migration of Central American adults (Massey et al, 2014; Quijada & Sierra, 2019).…”
Section: Related Literaturementioning
confidence: 99%
“…Youths’ ability to “make it” to a new country against multiple odds reflects their individual-level resources (e.g., belief in a higher power, grit, and cognitive flexibility) (Carlson, Cacciatore, and Klimek 2012). Research has documented that unaccompanied migrant youth score high on measures of hope, pathways (a sense of tangible goals), and agency (a belief in one’s ability to attain these goals) (Jani, Underwood, and Ranweiler 2016). Many young people also benefit from ecological sources of resilience, such as strong extended family systems, peer groups, connection to culture, and involvement in community-based organizations (Carlson, Cacciatore, and Klimek 2012; Rae-Espinoza 2016).…”
Section: Experiences Of Unaccompanied Migrant Youth Post-orr Custodymentioning
confidence: 99%